Analysis of optimization criteria for the process of switch displacement in a DC railroad turnout - Buriakovskyi, S. G.; Smirnov, V.; Asmolova, L. V.; Obruch, I. V.; Rafalskyi, O.; Maslii, Ar. S. (PC Tесhnology сеntеr, 2019)
This paper reports a study into the dynamics of displacing a railroad turnout's switches with a direct start of electric motor and a controlled DC electric drive in the MATLAB environment. The emphasis of simulation was the investigation of processes taking place in the kinematic links of a railroad turnout in the dynamics of its switch displacement. The estimation was based on the optimization criteria for a switch displacement process: the pulse of the impact of a switch against the frame rail, elasticity force in the working rod and a switch turning time. The result of the simulation of a non-controlled electric drive in a railroad turnout of switches has revealed that the values of these parameters are unsatisfactory. Mathematical models of the regulated electric drive for a railroad switch turnout were considered as two-mass electromechanical systems with subordinate regulation of basic coordinates and based on the principle of modal control. The results from mathematical modelling of the switch turning process convince that the numerical values of the optimization criteria for a regulated turning process are improved. Increasing the time of a regulated turning by up to 6 % of direct start results in a decreased impact in the kinematic links. Under the assumption of eliminating a technological gap in the reducer, a decrease in the impact of switches at the turning onset amounts to 6–8 %. At the same time, comparison of impacts at the onset of switch turning, when taking into consideration a technological gap in the reducer, as well as without it, shows a decrease in the elastic force amplitude by 250 %. The impact (a switch momentum pulse) could be reduced by 20–24 % upon turning completion. Our analysis of optimization criteria for the switch displacement process has demonstrated efficiency of the regulated electric drive compared to the direct start of an electric motor. That makes it possible not only to extend the operational functionality of a railroad switch turnout, but also to reduce costs for the current technical inspection, repairs in general, as well as to prolong the inter-repair period.

Досліджена динаміка переміщення гостряків стрілочного переводу з прямим пуском електродвигуна та регульованим електроприводом постійного струму в середовищі MATLAB. Фокус при моделюванні спрямовано на дослідження процесів, що відбуваються в кінематичних ланках стрілочного переводу в динаміці переміщення його гостряків. Оцінка здійснювалась за критеріями оптимізації процесу переміщення гостряків: імпульс удару гостряка об рамну рейку, пружність сили в робочій тязі та час переводу гостряка. У результаті моделювання нерегульованого електроприводу стрілочного переводу гостряків стало зрозуміло, що значення цих параметрів незадовільні. Математичні моделі регульованого електроприводу стрілочного переводу гостряків розглядались як двомасові електромеханічні системи з підлеглим регулюванням основних координат та за принципом модального керування. Результати математичного моделювання процесу переводу гостряків переконують у тому, що числові значення критеріїв оптимізації процесу регульованого переводу поліпшуються. При збільшенні часу регульованого переводу до 6 % від прямого пуску удар в кінематичних ланках зменшується. При припущенні щодо виключення технологічного зазору в редукторі, зменшення удару гостряків при початку переводу становить 6–8 %. Водночас, порівняння ударів на початку переводу гостряків з урахуванням технологічного зазору в редукторі та без нього показує зменшення амплітуди пружної сили на 250 %. Удар (імпульс моменту гостряків) при закінченні переводу може бути зменшено на 20–24 %. Аналіз критеріїв оптимізації процесу переміщення гостряків показав ефективність регульованого електроприводу у порівнянні із прямим пуском електродвигуна. Це дозволяє не тільки розширити функціональні можливості роботи стрілочного переводу гостряків, а і знизити затрати на поточний технічний огляд, ремонт у цілому, а також збільшення міжремонтного періоду.
Аналіз критеріїв оптимізації процесу переміщення гостряків стрілочного переводу постійного струму
Keywords: electromechanical system; DC electric motor; control system; displacement process optimization criteria; електромеханічні системи; електродвигуни; електрична енергія; напруга